Analysis of the Implementation of Civic Education toward Tolerance in the School Environment: Case Study in Class VIII SMP Negeri 1 Percut Sei Tuan - Thesia, Devi Putri; Siahaan, Parlaungan Gabriel; Purba, Novridah Reanti; Rahmadania, Jihan Aisyah; Gaol, Risky Sakti Lumban (Edumaspul: Jurnal Pendidikan, 2023)
Bullying is an act that often occurs in the school environment, which gives rise to conflict between students, thereby reducing students’ sense of tolerance. This research aims to find out how citizenship education is implemented towards an attitude of tolerance through learning citizenship education at SMP Negeri 1 Percut Sei Tuan in Class VIII- A. The method used in this research is descriptive qualitative. The sample in this research was 30 students in class VIII- A at SMP Negeri 1 Percut Sei Tuan. The data collection techniques used were interviews, giving questionnaires and documentation. The results of this research show that class VIII- A students at SMP Negeri 1 Percut Sei Tuan still often carry out body shaming bullying by saying their friends are fat which results in fights and saying bad words.